Healing Actions of Essential Oils from Citrus aurantium and d-Limonene in the Gastric Mucosa: The Roles of VEGF, PCNA, and COX-2 in Cell Proliferation - Moraes, Thiago Mello [UNESP]; Rozza, Ariane Leite [UNESP]; Kushima, Helio [UNESP]; Pellizzon, Claudia Helena [UNESP]; Machado Rocha, Lucia Regina [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP] (Mary Ann Liebert, Inc., 2013)
Previous studies have described the gastroprotective effects of essential oils that are derived from Citrus aurantium (OEC) and its main compound d-limonene (LIM) in a model of chemically induced ulcers in rats. However, these studies do not address the compound's healing effects on the gastric mucosa. Thus, the aim of this work was to evaluate the healing activity of OEC and LIM in acetic acid-induced gastric ulcers in rats, a model that reproduces human chronic ulcers. The obtained results demonstrated that lower effective doses of OEC (250mg/kg) and LIM (245mg/kg) induced gastric mucosal healing with a cure rate of 44% and 56%, respectively, compared with the control group (P<.05). During the 14 days of OEC or LIM treatment, none of the groups demonstrated toxicity in terms of body and organ weight or serum biochemical parameters. Both OEC and LIM treatment promoted an increase in epithelial healing, as confirmed by immunohistochemistry, which was greater in the animals that were treated with the positive control. In addition, both treatments increased cellular proliferation as measured by proliferating cell nuclear antigen and cyclooxygenase 2 expression in the gastric mucosa, vascular endothelial growth factor-mediated blood vessel formation in the margin of the ulcer, and production of gastric mucus, which fortifies the gastric protective barrier. We concluded that OEC and LIM, two common flavoring agents, promote gastric mucosal healing without any apparent toxic effect, resulting in better gastric epithelial organization in the treated rats.
Keywords: Citrus aurantium; essential oil; d-limonene; healing ulcer